Growth of Logarithmic Derivative of Meromorphic Functions - Latreuch, Zinelaâbidine; Belaïdi, Benharrat (Mathematica Scandinavica, 2013)
In this paper, we give some estimations about the growth of logarithmic derivative of meromorphic and entire functions and their applications in the theory of differential equations. We give also some examples to explain the sharpness of our results.